2023
DOI: 10.3390/pr11020353
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Methanol-Blocking Cation Exchange Membrane Modified with Graphene Oxide Nanosheet for Direct Methanol Fuel Cells

Abstract: Herein, graphene oxide nanosheets (GO) were synthesized and employed as an additive at various proportions to fabricate a novel cation exchange membrane based on grafted cellulose acetate with sodium 4-styrenesulfonate (GCA) via a solution casting method for direct methanol fuel cell (DMFC) applications. The structure of composite membranes has been examined using FTIR, TGA, SEM, and DSC. The physicochemical properties of the GCA/GO membranes, such as ion exchange capacity, water uptake, mechanical and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The chitosan/SiO 2 /sGO nanocomposite has shown a higher value of ionic conductivity (0.092 S cm –1 ) with a decent amount of ion-exchange capacity of 0.23 and was able to achieve a power density of 87.18 mW cm –2 in DMFC performance . Shalaby et al have shown the application of grafted cellulose acetate with the GO composite membrane to further reduce the methanol permeability and enhance the fuel cell performance. As a result of the interactions between the functionalities of the moieties present in their interface, the composite was able to achieve 5.99 × 10 –3 S cm –1 conductivity with 1.1 × 10 –7 cm 2 s –1 methanol permeability and, hence, the fuel cell performance of 31.85 mW cm –2 …”
Section: Energy Conversion Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chitosan/SiO 2 /sGO nanocomposite has shown a higher value of ionic conductivity (0.092 S cm –1 ) with a decent amount of ion-exchange capacity of 0.23 and was able to achieve a power density of 87.18 mW cm –2 in DMFC performance . Shalaby et al have shown the application of grafted cellulose acetate with the GO composite membrane to further reduce the methanol permeability and enhance the fuel cell performance. As a result of the interactions between the functionalities of the moieties present in their interface, the composite was able to achieve 5.99 × 10 –3 S cm –1 conductivity with 1.1 × 10 –7 cm 2 s –1 methanol permeability and, hence, the fuel cell performance of 31.85 mW cm –2 …”
Section: Energy Conversion Applicationsmentioning
confidence: 99%
“…Shalaby et al have shown the application of grafted cellulose acetate with the GO composite membrane to further reduce the methanol permeability and enhance the fuel cell performance. As a result of the interactions between the functionalities of the moieties present in their interface, the composite was able to achieve 5.99 × 10 –3 S cm –1 conductivity with 1.1 × 10 –7 cm 2 s –1 methanol permeability and, hence, the fuel cell performance of 31.85 mW cm –2 …”
Section: Energy Conversion Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cation exchange membranes (CEMs) are used in a wide variety of separation processes, such as electrodialysis, , diffusion dialysis, electrolyzers, and fuel cells . In these devices, CEMs act both as physical barriers between the anode and cathode and as cation carriers between the electrode redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cation exchange membranes (CEMs) are used in a wide variety of separation processes, such as electrodialysis, 1,2 diffusion dialysis, 3 electrolyzers, 4 and fuel cells. 5 In these devices, CEMs act both as physical barriers between the anode and cathode and as cation carriers between the electrode redox reactions. CEMs consist of a polymeric backbone, generally a styrenic, polyolefin, or acrylic, with tethered anionic groups, such as −SO 3 − , −COO − , and −PO 3 H − .…”
Section: Introductionmentioning
confidence: 99%